Sealing material for solid oxide fuel cell as well as preparation method and application of sealing material

By adjusting the composition of barium aluminosilicate-based glass and adding mica, the thermal expansion coefficient and fluidity of solid oxide fuel cell sealing materials are optimized, and the shortcomings of existing materials in high temperature environments are solved, and higher durability and Economical.

CN119419309AActive Publication Date: 2025-02-11成都烁克科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411496158.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-11
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing solid oxide fuel cell (SOFC) sealing materials have insufficient thermal expansion coefficient matching, chemical compatibility problems, uncertain durability and high production costs in high temperature environments.

Method used

Using sealing materials composed of mica and barium aluminosilicate-based glass, optimize the composition of the glass to reduce melting point and improve fluidity by adjusting the component ratio and adding elements such as B2O3 and CaO, and enhance the rigidity and resistance of the material by adding mica Pressure strength.

Benefits of technology

It realizes low softening point (690℃) and high thermal expansion coefficient (≥8×10-6/℃) of sealing materials, improves chemical compatibility and durability with other battery modules, and reduces production costs, suitable for medium-sized Low temperature SOFC sealing application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419309A_ABST
    Figure CN119419309A_ABST
Patent Text Reader

Abstract

The invention discloses a sealing material for a solid oxide fuel cell as well as a preparation method and application of the sealing material, and relates to the technical field of solid oxide fuel cells. The invention relates to a sealing material for a solid oxide fuel cell. The sealing material comprises mica and barium aluminum silicate-based glass, the barium aluminum silicate-based glass comprises the following components in percentage by mass: 10%-15% of BaO, 5%-10% of Al2O3, 15%-25% of B2O3, 6%-13% of CaO, less than or equal to 5% of La2O3 and the balance of SiO2. The sealing material obtained by adjusting the proportion of the components meets the requirements that the thermal expansion coefficient is larger than or equal to 8 * 10 <-6 > / DEG C and the softening point is low, thermal expansion coefficient matching and chemical stability are improved, chemical compatibility with other battery assemblies is good, long-term durability of sealing is ensured, production cost is reduced, and the sealing requirement of an SOFC stack is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid oxide fuel cells, and in particular to a sealing material for solid oxide fuel cells, a preparation method thereof, and an application thereof. Background Art

[0002] Solid Oxide Fuel Cell (SOFC) is an electrochemical power generation device with high efficiency and wide fuel range. In the field of sealing materials for solid oxide fuel cells, the existing technology mainly uses glass, glass ceramics and metal alloys as sealing materials. SOFC sealing materials work in a high temperature environment and are directly exposed to humid air and reducing fuel gas. They must remain stable and tightly combined with adjacent battery components for a long time to ensure that the fuel gas and the oxidizing gas do not mix during the operation of the solid oxide fuel cell to prevent fuel gas leakage. Their main function is to prevent the mixing of oxygen and fuel gas to avoid failure of the fuel cell or even explosion and other destructive behaviors. However, SOFC sealing materials still have some shortcomings in the current technology, including thermal stress and crack risks caused by poor matching of thermal expansion coefficients, chemical compatibility issues with other battery components under high temperature conditions, uncertain long-term durability, and high production costs. In addition, in order to ensure the durability of the seal, the manufacturing process of the sealing material is very complicated. These defects limit the large-scale application and economy of SOFC sealing materials. Based on this, the present application proposes a sealing material for solid oxide fuel cells and its preparation method and application. Summary of the invention

[0003] The main purpose of the present application is to provide a sealing material for a solid oxide fuel cell and a preparation method and application thereof, aiming to solve the technical problem that the performance of existing SOFC sealing materials needs to be improved.

[0004] To achieve the above-mentioned object, the present application proposes a sealing material for a solid oxide fuel cell, comprising mica and barium aluminosilicate-based glass;

[0005] The components of the barium aluminosilicate-based glass include, by mass percentage, BaO 10%-15%, Al2O3 5%-10%, B2O3 15%-25%, CaO 6%-13%, La2O3≤5% and the balance SiO2.

[0006] Optionally, the mass ratio of the mica to the barium aluminosilicate-based glass is 1:9.

[0007] Optionally, the mass ratio of the mica to the barium aluminosilicate-based glass is 1:4.

[0008] The present application also proposes a method for preparing a sealing material for a solid oxide fuel cell, comprising the following steps:

[0009] The mica is heated to remove crystal water, cooled, and then ball-milled to obtain mica powder;

[0010] BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 are mixed in proportion, heated to form glass and then kept warm to obtain glass paste; the glass paste is quenched and formed, annealed, and then crushed, ball-milled and sieved to obtain glass powder;

[0011] The mica powder and the glass powder are mixed, and a solvent is added to mix them evenly to obtain a finished sealing material.

[0012] Optionally, the step of heating the mica to remove crystal water comprises:

[0013] The mica is placed in an electric furnace and heated at a temperature of 800°C-900°C for 5h-7h to remove crystal water.

[0014] Optionally, the step of mixing BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 in a proportion, heating and forming glass, and then keeping the mixture warm to obtain a glass paste comprises:

[0015] BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 powder raw materials with purity ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1450℃-1650℃ at a heating rate of 4℃ / min-6℃ / min. After forming glass, keep warm for 9h-11h to obtain glass paste.

[0016] Optionally, the step of annealing the glass paste after quenching and forming the glass paste comprises:

[0017] After the glass paste is quenched and formed on a graphite plate, it is immediately placed in an annealing furnace and kept at 580° C.-780° C. for 7 h-9 h, and then cooled to room temperature.

[0018] Optionally, the glass powder has a particle size of less than 45 μm.

[0019] Optionally, the solvent is a mixture of 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate in a mass ratio of (3.5-7.5):(4-6):(3.5-7.5):(4-6).

[0020] The present application also proposes an application of a sealing material for a solid oxide fuel cell, wherein the sealing material is used for sealing a metal connector of a solid oxide fuel cell.

[0021] This application at least includes the following beneficial effects:

[0022] The present application is based on barium aluminosilicate-based glass as a sealing matrix material for SOFC. By changing the composition ratio and adding elements that can reduce the melting point and improve fluidity, the composition and content of the barium aluminosilicate-based glass are optimized to be: BaO 10%-15%, Al2O3 5%-10%, B2O3 15%-25%, CaO 6%-13%, La2O3≤5% and the balance SiO2, which reduces the SiO2 content in the barium aluminosilicate-based glass, optimizes the B2O3 composition and reduces the BaO ratio, increases the B2O3 content, and adjusts the ratio of CaO and La2O3;

[0023] Since SiO2 is the main skeleton component of glass, although it provides excellent mechanical strength and chemical stability, its melting point is relatively high, about 1710°C. If its content is too high, the melting point of the entire glass will be too high, affecting the melt fluidity and sintering properties during the preparation process. By appropriately reducing the SiO2 content, the melting point of the glass can be significantly reduced, making it easier to sinter at a lower temperature while maintaining sufficient structural stability; B2O3 can be used as a glass network flux, which has a lower melting point (about 450°C) and can improve the fluidity of the glass. Increasing the B2O3 content can effectively reduce the melting point of the glass, making it more suitable for the melting process; BaO may cause chemical instability at high temperatures, especially when in contact with other materials (such as electrolytes or electrodes), which may induce reactions or form unfavorable phases. By reducing the proportion of BaO, these instabilities can be reduced and the long-term stability of the sealing material can be enhanced. Excessive BaO content may cause thermal expansion mismatch, thereby inducing stress and cracks in thermal cycles. , optimizing the composition of B2O3 and reducing BaO can better match the thermal expansion characteristics of the sealing material and other components, reduce stress concentration, and reducing the BaO content can also help improve the overall mechanical properties and electrical insulation properties of the sealing material; La2O3 has a high melting point and CaO has a relatively low melting point. By reducing the proportion of La2O3 and increasing CaO, the overall melting point of the glass can be effectively reduced. Both La and Ca can be used as glass network modifiers to destroy the Si-O network, reduce viscosity and increase the fluidity of the glass material when molten. Both can combine with oxygen to form stable compounds. Adjusting the La / Ca molar ratio within a certain range will not significantly change the basic properties of the glass. Its effects on thermal stability and thermal expansion coefficient can offset each other, so that the overall glass performance is still suitable for the use conditions of SOFC after the change. The increase in CaO makes the glass easier to flow at high temperatures, ensuring its good sealing performance and uniform filling effect. At the same time, it can also reduce the use of rare earth raw material La2O3 and save costs;

[0024] By adding mica, an inorganic particle mixture, glass and mica form a glass-ceramic composite, which can enhance the rigidity and compressive strength of the sealing material, effectively fill the micropores of the glass, reduce gas permeation, improve the high-temperature stability and filling capacity of the sealing material, thereby reducing the stress caused by thermal expansion and improving the durability of the sealing material in the battery environment;

[0025] The sealing material obtained by adjusting the composition ratio in this application finally reaches a thermal expansion coefficient of ≥8×10 -6 / ℃ and low softening point (690℃) requirements, improves thermal expansion coefficient matching and chemical stability, has good chemical compatibility with other battery components, ensures long-term durability of the seal, and reduces production costs, meeting the requirements of SOFC cell stack sealing. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0027] Figure 1 This is a cross-sectional microstructure diagram of the sealing material after sintering and crystallization according to the embodiment of the present application;

[0028] Figure 2 A schematic diagram of thermal expansion curves of the sealing material sample and other SOFC components described in the embodiment of the present application;

[0029] Figure 3 A schematic diagram of a curve showing changes in viscosity and height of a sealing material sample according to an embodiment of the present application as a function of temperature;

[0030] Figure 4 A schematic diagram of a resistance change curve of a sealing material sample according to an embodiment of the present application;

[0031] Figure 5 Schematic diagram of the high temperature cycle leakage rate of the sealing material sample described in the embodiment of the present application.

[0032] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In view of the technical problems existing in the above-mentioned prior art, the embodiments of the present application provide a sealing material for a solid oxide fuel cell, including mica and barium aluminum silicate-based glass;

[0035] The components of the barium aluminosilicate-based glass include, by mass percentage, BaO 10%-15%, Al2O3 5%-10%, B2O3 15%-25%, CaO 6%-13%, La2O3≤5% and the balance SiO2.

[0036] In view of the current trend of solid oxide fuel cells developing towards medium and low temperature (<800°C) operating temperatures, and in order to match medium and low temperature solid oxide fuel cells, the present application is based on barium aluminosilicate-based glass as a SOFC sealing matrix material, and optimizes the composition and content of the barium aluminosilicate-based glass by changing the component ratio and adding elements that can lower the melting point and increase fluidity: BaO 10%-15%, Al2O3 5%-10%, B2O3 15%-25%, CaO 6%-13%, La2O3≤5% and the remainder SiO2, which reduces the SiO2 content in the barium aluminosilicate-based glass, optimizes the B2O3 composition and reduces the BaO ratio, increases the B2O3 content, and adjusts the ratio of CaO and La2O3. SiO2 is the main skeleton component of glass. Reducing its proportion can reduce the melting point, but still maintain the strength and stability of the glass; BaO can keep the thermal expansion coefficient of the sealing material matching, and reducing a certain proportion can reduce the melting point of the sealing material; Al2O3, as an inorganic particle, can increase the mechanical strength and chemical resistance of the sealing material; B2O3 can provide fluxing, reduce the melting point and improve fluidity. Increasing the B2O3 content can effectively reduce the melting point of the glass, making it more suitable for the melting process; CaO can provide thermal shock resistance and adjust the melting point of the glass. La2O3 can enhance the reduction resistance and high temperature stability of the sealing material. La and Ca have similar chemical properties and Function, by reducing the proportion of La2O3 and increasing CaO, the overall melting point of the glass can be effectively reduced, and its effects on thermal stability and thermal expansion coefficient can offset each other, so that the overall glass performance is still suitable for SOFC use conditions after the change; at the same time, increasing B2O3 and CaO can effectively improve the fluidity of the glass in a molten state, ensuring that the material can better fill the contact interface during the sintering process and improve the sealing; reducing SiO2, increasing B2O3 and CaO, the overall melting point of the glass will be reduced, so that it can be sintered at a lower temperature, which is helpful for energy saving and consumption reduction in actual production, and avoiding thermal damage to other components of the SOFC battery stack. Adding mica, an inorganic particle mixture, the glass and mica form a glass-ceramic composite, which can enhance the rigidity and compressive strength of the sealing material, effectively fill the micropores of the glass, reduce gas permeation, and improve the high temperature stability and filling capacity of the sealing material, thereby reducing the stress caused by thermal expansion and improving the durability of the sealing material in the battery environment. The sealing material obtained by adjusting the proportion of the components in this application finally reaches a thermal expansion coefficient of ≥8×10 -6 / ℃ and low softening point (690℃) requirements solve the problems of thermal expansion coefficient mismatch, poor chemical compatibility with other battery components, uncertain long-term durability and high production cost, and have good applicability in medium and low temperature (<800℃) SOFC sealing applications.

[0037] Specifically, the mica is phlogopite, and its molecular formula is KMg3(AlSiO10 )(OH)2.

[0038] As an implementation method of the present application, the mass ratio of the mica to the barium aluminum silicate-based glass is 1:9.

[0039] Specifically, mica as ceramic particles can provide excellent thermal stability and good mechanical properties. A reasonable glass / ceramic ratio can lower the melting point, ensure good fluidity and filling capacity at high temperatures, effectively improve the high-temperature stability of the sealing material, and adapt to the working conditions of SOFC. Mica has good chemical stability and can improve the durability of the sealing material in the battery environment.

[0040] When the mass ratio of mica to glass is 1:9, the toughness of SOFC sealing materials can be improved to a certain extent, and the thermal expansion coefficient can reach ≥8×10 -6 / ℃ and softening point 690℃ requirements, can be well matched with other SOFC components, avoid sealing failure due to thermal expansion mismatch, and has suitable high temperature viscosity, and its high temperature resistance value meets the conductivity requirements of SOFC high temperature sealing materials.

[0041] As an implementation method of the present application, the mass ratio of the mica to the barium aluminum silicate-based glass is 1:4. When the mass ratio of mica to glass is 1:4, the toughness of the SOFC sealing material can be greatly improved, and at the same time, it has a good thermal expansion coefficient and can be well matched with other components of the SOFC. When the mass ratio of mica to glass is 1:4, the SOFC sealing material has an optimal high-temperature viscosity, which can ensure good adhesion between the sealing material and its adjacent components, and maintain the integrity of the structure during high-temperature operation, thereby forming a good seal, and its high-temperature resistance value and average leakage rate meet the requirements of SOFC cell stack sealing.

[0042] The embodiment of the present application also provides a method for preparing a sealing material for a solid oxide fuel cell, comprising the following steps:

[0043] The mica is heated to remove crystal water, cooled, and then ball-milled to obtain mica powder;

[0044] BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 are mixed in proportion, heated to form glass and then kept warm to obtain glass paste; the glass paste is quenched and formed, annealed, and then crushed, ball-milled and sieved to obtain glass powder;

[0045] The mica powder and the glass powder are mixed, and a solvent is added to mix them evenly to obtain a finished sealing material.

[0046] The present application adopts a melting process to prepare a sealing material, with Al2O3, La2O3 and mica as ceramic components, BaO, B2O3, SiO2, etc. as glass components, and CaO as inorganic particles. During the heat treatment process, the bonding and interaction between particles can be promoted, the porosity in the sealing material can be reduced, the overall density and strength can be improved, and the microstructure of the sealing material can be made more uniform, and the performance stability can be improved. Mica is then mixed with glass to form a glass-ceramic composite, so that the mica particles can effectively fill the micropores of the glass, further improving the good fluidity and filling capacity of the sealing material at high temperatures.

[0047] As an implementation method of the present application, the step of heating mica to remove crystal water includes:

[0048] The mica is placed in an electric furnace and heated at a temperature of 800°C-900°C for 5h-7h to remove crystal water.

[0049] As an implementation method of the present application, the step of mixing BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 in a proportion, heating and forming glass, and then keeping the temperature to obtain a glass paste includes:

[0050] BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 powder raw materials with purity ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1450℃-1650℃ at a heating rate of 4℃ / min-6℃ / min. After forming glass, keep warm for 9h-11h to obtain glass paste.

[0051] Preferably, heating to 1550°C at a heating rate of 5°C / min and keeping warm for 10 hours after forming glass helps the bonding and interaction between the components, reduces the porosity in the material, improves the density, makes the microstructure of the glass more uniform, improves the performance stability, and improves its filling capacity in sealing applications.

[0052] As an implementation method of the present application, the step of annealing the glass paste after quenching and forming the glass paste comprises:

[0053] After the glass paste is quenched and formed on a graphite plate, it is immediately placed in an annealing furnace and kept at 580° C.-780° C. for 7 h-9 h, and then cooled to room temperature.

[0054] Preferably, annealing is performed at 680° C. for 8 hours to release internal stress and make the microstructure of the sealing material more uniform, thereby improving performance stability.

[0055] As an implementation method of the present application, the particle size of the glass powder is less than 45 μm. By controlling the particle size of the glass powder, the sealing material can flow more easily at high temperatures, which helps it achieve a better filling effect in sealing applications.

[0056] As an implementation method of the present application, the solvent is a mixture of 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate in a mass ratio of (3.5-7.5):(4-6):(3.5-7.5):(4-6).

[0057] An embodiment of the present application also provides an application of a sealing material for a solid oxide fuel cell, wherein the sealing material is used for sealing a metal connector of a solid oxide fuel cell.

[0058] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0059] Example 1

[0060] A sealing material for a solid oxide fuel cell is prepared by the following steps:

[0061] The mica was placed in an electric furnace and heated at 850° C. for 6 h to remove crystal water, then cooled and ball-milled to obtain mica powder;

[0062] 25g BaO, 15g Al2O3, 40g B2O3, 19g CaO, 10g La2O3 and 90g SiO2 powder raw materials with a purity of ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1550°C at a heating rate of 5°C / min, and kept warm for 10 hours after forming glass to obtain a glass paste; the glass paste is quenched and formed on a graphite plate, immediately placed in an annealing furnace and kept warm at 680°C for 8 hours, cooled to room temperature, crushed, ball-milled and sieved to obtain a glass powder with a particle size of less than 45μm;

[0063] The mica powder and the glass powder are mixed in a mass ratio of 1:9, and a solvent is added for mixing, wherein the solvent is 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate mixed in a mass ratio of 5.5:5:5.5:5 to obtain a finished sealing material.

[0064] Example 2

[0065] A sealing material for a solid oxide fuel cell is prepared by the following steps:

[0066] The mica was placed in an electric furnace and heated at 850° C. for 6 h to remove crystal water, then cooled and ball-milled to obtain mica powder;

[0067] 25g BaO, 15g Al2O3, 40g B2O3, 19g CaO, 10g La2O3 and 90g SiO2 powder raw materials with a purity of ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1550°C at a heating rate of 5°C / min, and kept warm for 10 hours after forming glass to obtain a glass paste; the glass paste is quenched and formed on a graphite plate, immediately placed in an annealing furnace and kept warm at 680°C for 8 hours, cooled to room temperature, crushed, ball-milled and sieved to obtain a glass powder with a particle size of less than 45μm;

[0068] The mica powder and the glass powder are mixed in a mass ratio of 1:4, and a solvent is added for mixing, wherein the solvent is 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate mixed in a mass ratio of 5.5:5:5.5:5 to obtain a finished sealing material.

[0069] Example 3

[0070] A sealing material for a solid oxide fuel cell is prepared by the following steps:

[0071] The mica was placed in an electric furnace and heated at 850° C. for 6 h to remove crystal water, then cooled and ball-milled to obtain mica powder;

[0072] 20g BaO, 10g Al2O3, 40g B2O3, 22g CaO, 8g La2O3 and 100g SiO2 powder raw materials with a purity of ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1550°C at a heating rate of 5°C / min, and kept warm for 10 hours after forming glass to obtain a glass paste; the glass paste is quenched and formed on a graphite plate, immediately placed in an annealing furnace and kept warm at 680°C for 8 hours, cooled to room temperature, crushed, ball-milled and sieved to obtain a glass powder with a particle size of less than 45μm;

[0073] The mica powder and the glass powder are mixed in a mass ratio of 1:9, and a solvent is added for mixing, wherein the solvent is 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate mixed in a mass ratio of 5.5:5:5.5:5 to obtain a finished sealing material.

[0074] Example 4

[0075] A sealing material for a solid oxide fuel cell is prepared by the following steps:

[0076] The mica was placed in an electric furnace and heated at 850° C. for 6 h to remove crystal water, then cooled and ball-milled to obtain mica powder;

[0077] 22g BaO, 20g Al2O3, 42g B2O3, 26g CaO, 10g La2O3 and 80g SiO2 powder raw materials with a purity of ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1550°C at a heating rate of 5°C / min, and kept warm for 10 hours after forming glass to obtain a glass paste; the glass paste is quenched and formed on a graphite plate, immediately placed in an annealing furnace and kept warm at 680°C for 8 hours, cooled to room temperature, crushed, ball-milled, and sieved to obtain a glass powder with a particle size of less than 45μm;

[0078] The mica powder and the glass powder are mixed in a mass ratio of 1:4, and a solvent is added for mixing, wherein the solvent is 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate mixed in a mass ratio of 5.5:5:5.5:5 to obtain a finished sealing material.

[0079] Comparative Example 1

[0080] A sealing material for a solid oxide fuel cell is prepared by the following steps:

[0081] 25g BaO, 15g Al2O3, 40g B2O3, 19g CaO, 10g La2O3 and 90g SiO2 powder raw materials with a purity of ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1550°C at a heating rate of 5°C / min, and kept warm for 10 hours after forming glass to obtain a glass paste; the glass paste is quenched and formed on a graphite plate, immediately placed in an annealing furnace and kept warm at 680°C for 8 hours, cooled to room temperature, crushed, ball-milled and sieved to obtain a glass powder with a particle size of less than 45μm;

[0082] A solvent is added to the glass powder and mixed evenly, wherein the solvent is 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate mixed in a mass ratio of 5.5:5:5.5:5 to obtain a finished sealing material.

[0083] Experimental example

[0084] (I) Microstructure observation

[0085] The sealing materials in Example 1, Example 2 and Comparative Example 1 were dried at 120°C, and then subjected to ball milling and sieving granulation procedures. The resulting powders were placed in a mold and pressed at a pressure of 270 MPa for 60 seconds to form cylindrical samples with a diameter of 8 mm and a height of 20 mm. The samples were then placed in a high-temperature furnace, heated to 830°C at a heating rate of 5°C / min, and kept warm for 1 hour for sintering, then cooled to 750°C and kept warm for 4 hours for crystallization. The crystallized samples were cut, ground, and polished, and the microstructure of the samples was observed with a metallographic microscope, using a 10x objective magnification, and the images were recorded by CCD. The results are shown in FIG. Figure 1 As shown, Figure 1 In the figure, part (a) is the microstructure diagram of the sample in comparative example 1; part (b) is the microstructure diagram of the sample in embodiment 1; and part (c) is the microstructure diagram of the sample in embodiment 2.

[0086] Depend on Figure 1 It can be seen that in parts (b) and (c), mica is uniformly dispersed in the glass matrix, while cracks appear in part (a). This is because glass materials are prone to embrittlement under tensile stress and are therefore prone to cracking. In Examples 1 and 2, by adding a certain amount of mica, the expansion of the cracks is suppressed, and when the mass ratio of mica to glass is 1:4, the toughness of the sealing material is greatly improved.

[0087] (II) Thermal expansion coefficient measurement

[0088] The crystallized sample in Experimental Example (I) was cut and ground to make a sample with parallel upper and lower surfaces, and then placed in a high-temperature thermal expansion instrument. Argon was used as the protective atmosphere, and the temperature was increased at a rate of 5°C / min and a load of 1g. The temperature and elongation of the sample were recorded in real time by a computer. The results are shown in Figure 1. Figure 2 shown.

[0089] Depend on Figure 2It can be seen that with the increase of temperature, the thermal expansion coefficient of each sample gradually increases, and the thermal expansion curve of the sample in Example 2 within the temperature measurement range shows a near-linear behavior, the curve is smooth and there is no obvious inflection point. This near-linear behavior means that within a smaller temperature range, the thermal expansion coefficient of the material (volume change rate under temperature change) can be approximated as a constant and does not fluctuate significantly with temperature changes. In addition, the thermal expansion coefficient of the sample in Example 2 is between 7.74ppm / ℃-11.8ppm / ℃ (RT-600℃), and it shows similar thermal expansion behavior with other components of SOFC (bipolar plates and metal connectors), indicating that the sample in Example 2 has excellent thermal matching with other components of SOFC, indicating that the present application can fine-tune the thermal expansion coefficient of the glass to a certain extent by optimizing the glass composition and adding a certain amount of mica, so that it can still match well with other components of SOFC, avoiding sealing failure caused by thermal expansion mismatch.

[0090] (III) High temperature viscosity measurement

[0091] High temperature viscosity is a key parameter of glass ceramic sealants used in the SOFC sealing process. Suitable glass or glass ceramic sealants for SOFC stacks must provide sufficient viscosity and mechanical strength to ensure good adhesion between the sealant and its adjacent components and maintain structural integrity during high temperature operation. The effects of high temperature viscosity on SOFC glass sealing materials include: 1. Sealing performance: The ideal viscosity can ensure that the glass sealing material is sufficiently fluid when heated to fill the gaps between the battery components to form a good seal. If the viscosity is too high, the glass may not flow sufficiently, resulting in incomplete sealing and leakage risks; 2. Thermomechanical matching: The viscosity of the glass sealant affects its thermal expansion behavior. The appropriate viscosity can help the glass match the expansion coefficient of other battery materials during heating and cooling, reducing the possibility of thermal stress and cracking; 3. Processability: Viscosity affects the processing and operation difficulty of the glass sealant. Lower viscosity usually means better fluidity, which is convenient for coating and molding in production, but if it is too low, it may flow and lead to an unstable sealing structure; 4. Structural integrity: During use, the viscosity of the glass affects its ability to resist corrosion in an oxidizing environment. The appropriate viscosity helps to maintain the structural integrity of the sealant and extend its service life.

[0092] The sealing materials in Example 1, Example 2 and Comparative Example 1 were dried at 120°C, and then subjected to ball milling and sieving granulation procedures. The resulting powders were placed in a mold and pressed at a pressure of 270 MPa for 60 seconds to form cylindrical samples with a diameter of 8 mm and a height of 6 mm. The cylindrical samples were then placed in a high-temperature parallel plate viscometer, a load of 0.025 MPa was applied, and the samples were heated to 850°C at a heating rate of 5°C / min. The changes in the viscosity and height of the samples with temperature were recorded. The results are shown in FIG. Figure 3shown.

[0093] Depend on Figure 3 It can be seen that under a specific external load (0.025MPa), the viscosity and height of each sample change with the change of temperature; all samples show a reflection point when the temperature is close to or exceeds their crystal temperature, which indicates that during the heating process, the two mechanisms of softening and hardening are competing; the viscosity of the sample of comparative example 1 is significantly reduced when the temperature is higher than the glass transition temperature; compared with comparative example 1, the viscosity of the samples of examples 1 and 2 is higher, and the viscosity of the sample of example 2 is higher than that of example 1, which indicates that in examples 1 and 2, by adding a certain amount of mica, it is beneficial to improve the viscosity of the sealing material, and when the mass ratio of mica to glass is 1:4, the viscosity of the sealing material is higher.

[0094] (IV) High temperature resistance measurement

[0095] The sealing materials in Example 1, Example 2 and Comparative Example 1 were dried at 120°C, and then subjected to ball milling and sieving granulation procedures. The resulting powders were placed in a mold and pressed at a pressure of 270 MPa for 60 seconds to form a sheet sample with a thickness of 1 mm. The sheet sample was then placed in a high-temperature furnace, heated to 830°C at a heating rate of 5°C / min, and kept warm for 1 hour for sintering. Ag glue was coated on both sides of the sintered sheet sample as conductive electrodes, and placed in a high-temperature furnace at 800°C to maintain the temperature. The two-point four-wire method was used to record the change in its resistance value with the temperature holding time. The results are shown in FIG. Figure 4 shown.

[0096] Depend on Figure 4 It can be seen that in air at 800°C, the samples were measured for more than 2700 hours, and the resistance of the samples in Example 2 and Comparative Example 1 increased with the increase of test time. In the long-term test, the resistance values ​​reached 289kΩ and 391kΩ, respectively. The resistance of the sample in Example 1 changed smoothly, and the resistance was about 69kΩ, which means that the resistance of each sample was much higher than the resistance of the SOFC metal connector. The sealing material obtained by optimizing the glass composition in the present application has good applicability in SOFC sealing applications.

[0097] (V) High temperature thermal cycle seal leakage rate measurement

[0098] The sealing material in Example 2 was coated between the upper and lower Crofer22APU stainless steel (ThyssenKrupp VDMGmbH, Germany) substrates, and after a high temperature curing process, a rectangular hollow structure sample with a sealing range of 0.5mm in height, 7mm in width and 45mm in side length was made. A hole was opened in the upper substrate to allow gas to pass through. After applying a stress of 0.031MPa to the test sample and passing 2psi of He gas, the temperature was repeatedly raised and lowered between room temperature and 800℃, with a heating / cooling rate of 2℃ / min. The total time of maintaining the temperature at 800℃ was more than 1 hour. The change of sealing pressure with the holding time was recorded, and its leakage rate was calculated. The results are shown in FIG. Figure 5 shown.

[0099] Depend on Figure 5 It can be seen that after the sealing material in Example 2 and the Crofer22APU stainless steel metal connector were bonded and cured at high temperature, the average leakage rate was 2.1×10 -4 mbar·l / s / cm, which is lower than the permissible upper limit of 5.2×10 -4 mbar·l / s / cm, indicating that the sealing material of the present application has good sealing performance and is suitable for sealing of SOFC.

[0100] In summary, the present application is based on barium aluminum silicate-based glass, and by changing the composition ratio and adding elements that can reduce the melting point and improve fluidity, the molar ratio of La / Ca is adjusted, the use of rare earth raw material La2O3 is reduced, the B2O3 composition is optimized and the BaO ratio is reduced, and an inorganic particle mixture mica is added. The sealing material is prepared by a melting process, and the thermal expansion coefficient is ≥8×10 -6 / ℃ and softening point 690℃, and the resistance values ​​of the samples with mica and glass mixed ratio of 1:4 and 1:9 in high temperature (800℃) and long time (>2700 hours) tests were 289kΩ and 69kΩ respectively, which met the conductivity requirements of SOFC high temperature packaging materials; the sealing material with mica and glass mixed ratio of 1:4 was bonded and cured with Crofer22APU stainless steel substrate at high temperature, and passed 50 thermal cycle (RT-800℃) leakage tests, with an average leakage rate of 2.1×10 -4 mbar·l / s / cm, which is lower than the allowable upper limit (5.2×10 -4 mbar·l / s / cm), which meets the sealing requirements of SOFC cell stack.

[0101] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made by using the contents of the present application specification and drawings under the inventive concept of the present application, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A sealing material for a solid oxide fuel cell, characterized in that: including mica and barium aluminosilicate based glasses; The components of the barium aluminosilicate-based glass include, by mass percentage, BaO 10%-15%, Al2O3 5%-10%, B2O3 15%-25%, CaO 6%-13%, La2O3≤5% and the balance SiO2.

2. The sealing material for solid oxide fuel cells according to claim 1, characterized in that: The mass ratio of the mica to the barium aluminosilicate-based glass is 1:

9.

3. The sealing material for solid oxide fuel cell according to claim 1, characterized in that: The mass ratio of the mica to the barium aluminosilicate-based glass is 1:

4.

4. A method for preparing a sealing material for a solid oxide fuel cell according to any one of claims 1 to 3, characterized in that: The following steps are involved: The mica is heated to remove crystal water, cooled, and then ball-milled to obtain mica powder; BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 are mixed in proportion, heated to form glass and then kept warm to obtain glass paste; the glass paste is quenched and formed, annealed, and then crushed, ball-milled and sieved to obtain glass powder; The mica powder and the glass powder are mixed, and a solvent is added to mix them evenly to obtain a finished sealing material.

5. The method for preparing a sealing material for a solid oxide fuel cell according to claim 4, characterized in that: The step of heating mica to remove crystal water comprises: The mica is placed in an electric furnace and heated at a temperature of 800°C-900°C for 5h-7h to remove crystal water.

6. The method for preparing a sealing material for a solid oxide fuel cell according to claim 4, characterized in that: The step of mixing BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 in a proportion, heating and forming glass and then keeping the temperature to obtain glass paste comprises: BaO, Al2O3, B2O3, CaO, La2O3 and SiO2 powder raw materials with purity ≥99.5% are mixed according to a proportion, placed in an electric furnace and heated to 1450℃-1650℃ at a heating rate of 4℃ / min-6℃ / min. After forming glass, keep warm for 9h-11h to obtain glass paste.

7. The method for preparing a sealing material for a solid oxide fuel cell according to claim 4, characterized in that: The step of annealing the glass paste after quenching and forming the glass paste comprises: After the glass paste is quenched and formed on a graphite plate, it is immediately placed in an annealing furnace and kept at 580° C.-780° C. for 7 h-9 h, and then cooled to room temperature.

8. The method for preparing a sealing material for a solid oxide fuel cell according to claim 4, characterized in that: The particle size of the glass powder is less than 45 μm.

9. The method for preparing a sealing material for a solid oxide fuel cell according to claim 4, characterized in that: The solvent is a mixture of 96% ethanol, butanone, polyvinyl butyral and diisononyl phthalate in a mass ratio of (3.5-7.5): (4-6): (3.5-7.5): (4-6).

10. An application of a sealing material for a solid oxide fuel cell according to any one of claims 1 to 3, characterized in that: The sealing material is used for sealing metal interconnects of solid oxide fuel cells.

Citation Information

Patent Citations

  • Sealing material used for solid oxide fuel battery and method for making same

    CN1929163A

  • A sealing materials contained alumina particle for solid oxide fuel cell

    KR1020090052566A

  • Manufacturing method of the glass-ceramics gasket for solid oxide fuel cell

    KR1020120021924A

  • Multi-layer seal for electrochemical devices

    US20030203267A1

  • Sealant glass composition and solid oxide fuel cell using same

    US20220024809A1